Rickettsial pathogen inhibits tick cell death through tryptophan metabolite mediated activation of p38 MAP kinase - Prachi Namjoshi; Mustapha Dahmani; Hameeda Sultana; Girish Neelakanta (iScience, 2023)
Summary: Anaplasma phagocytophilum modulates various cell signaling pathways in mammalian cells for its survival. In this study, we report that A. phagocytophilum modulates tick tryptophan pathway to activate arthropod p38 MAP kinase for the survival of both this bacterium and its vector host. Increased level of tryptophan metabolite, xanthurenic acid (XA), was evident in A. phagocytophilum-infected ticks and tick cells. Lower levels of cell death markers and increased levels of total and phosphorylated p38 MAPK was noted in A. phagocytophilum-infected ticks and tick cells. Treatment with XA increased phosphorylated p38 MAPK levels and reduced cell death in A. phagocytophilum-infected tick cells. Furthermore, treatment with p38 MAPK inhibitor affected bacterial replication, decreased phosphorylated p38 MAPK levels and increased tick cell death. However, XA reversed these effects. Taken together, we provide evidence that rickettsial pathogen modulates arthropod tryptophan and p38 MAPK pathways to inhibit cell death for its survival in ticks.